Molecular mechanisms of osteosarcoma metastasis and possible treatment opportunities - Du, Xinhui; Wei, Hua; Zhang, Boya; Wang, Bangmin; Li, Zhehuang; Pang, Lon Kai; Zhao, Ruiying; Yao, Weitao (Frontiers in Oncology, 2023)
In osteosarcoma patients, metastasis of the primary cancer is the leading cause of death. At present, management options to prevent metastasis are limited and non-curative. In this study, we review the current state of knowledge on the molecular mechanisms of metastasis and discuss promising new therapies to combat osteosarcoma metastasis. Genomic and epigenomic changes, metabolic reprogramming, transcription factors, dysregulation of physiologic pathways, and alterations to the tumor microenvironment are some of the changes reportedly involved in the regulation of osteosarcoma metastasis. Key factors within the tumor microenvironment include infiltrating lymphocytes, macrophages, cancer-associated fibroblasts, platelets, and extracellular components such as vesicles, proteins, and other secreted molecules. We conclude by discussing potential osteosarcoma-limiting agents and their clinical studies.